From spontaneous rhythmic engagement to joint drumming: A gradual development of flexible coordination at approximately 24 months of age - Yu, Lira; Todoriki, Kaho; Myowa, Masako (Frontiers in Psychology, 2022)
Humans have a flexible and accurate ability to coordinate their movement in time with external rhythms. However, it remains unclear when and how, during their development, human children acquire the ability to adjust tempo and control the timing of their movement toward others. A previous study suggested that such self-regulation of coordination develops at around 18 and 30 months after birth. In this study, we investigated the performance of 24-month-old children and compared their data with those of 18- and 30-month-olds provided in our previous study (Yu & Myowa, 2021). In the joint-drumming task, each child was enticed to drum under four conditions (partner: mother or robot; speed: 400 or 600 ms inter-stimulus-interval (ISI)). The most pivotal test condition was the 600 ms ISI speed condition (slower than children’s spontaneous motor tempo in these age groups). We found that from the age of 24 months, children try to slow down their drumming tempo toward the 600 ms ISI speed condition, regardless of the drumming partner. On the other hand, significant timing control toward the onset of the 600 ms ISI condition was observed from the age of 30 months. This implies that both motor and cognitive mechanisms are required for flexible tempo adjustment and accurate synchronization and that these develop gradually among 18-, 24-, and 30-month-olds.